2020
DOI: 10.1186/s12888-020-02786-8
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and preventive measures during the COVID-19 outbreak in Taiwan

Abstract: Background It is hypothesized that anxiety and behavioral responses are intense at the beginning of an epidemic. The objective of this study was to investigate anxiety symptoms and use of preventive measures against COVID-19. The study also compared the association between preventive measures and anxiety symptoms during the week immediately preceding the study and those symptoms and measures at the beginning of the outbreak. Methods A cross-sectional population survey u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
66
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 33 publications
(28 reference statements)
16
66
1
7
Order By: Relevance
“…Although some studies have found that mask wearing could create a false sense of security among some individuals ( Goh, Y., et al, 2020 ), public health education also needs to put more emphasis on these aspects to effectively fight anxiety during the COVID-19 pandemic among Chinese population. Another previous study found higher anxiety being associated with an increased use of preventive measures against COVID-19 through a cross-sectional population survey involved 3555 residents of Taiwan aged between 20 to 70 years ( Wong, L.P., et al, 2020 ). We also think that the shortages of supplies, rising prices and increasingly frantic quests for surgical masks during the COVID-19 epidemic ( Choi, E.P.H., et al, 2020 ) may confound the association between mask wearing and the risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found that mask wearing could create a false sense of security among some individuals ( Goh, Y., et al, 2020 ), public health education also needs to put more emphasis on these aspects to effectively fight anxiety during the COVID-19 pandemic among Chinese population. Another previous study found higher anxiety being associated with an increased use of preventive measures against COVID-19 through a cross-sectional population survey involved 3555 residents of Taiwan aged between 20 to 70 years ( Wong, L.P., et al, 2020 ). We also think that the shortages of supplies, rising prices and increasingly frantic quests for surgical masks during the COVID-19 epidemic ( Choi, E.P.H., et al, 2020 ) may confound the association between mask wearing and the risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, an online questionnaire commenced on February 14, 2020. Of 3,555 adults, 52.1% reported moderate to severe anxiety symptoms [5]. As such, other studies have investigated anxiety during the COVID-19 pandemic, but no previous research has specifically investigated daily life changes or changes in work among editors or publishing staff.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, debe destacarse que las mujeres se reconocieron en una mayor proporción como población vulnerable, refiriendo una mayor exposición a la violencia doméstica, así como a índices más altos de trastornos afectivos (ansiedad, estrés y depresión), como lo reportan otros estudios (Lin et al, 2020;Mazza, De Lorenzo et al, 2020;Özdin & Bayrak Özdin, 2020;Pappa, 2020;Qiu et al, 2020;Savitsky et al, 2020;Wong et al, 2020).…”
Section: Discussionunclassified
“…Creada para atender problemas de abuso de sustancias y de adicciones, bajo la coordinación de la Comisión Nacional contra las Adicciones (CONADIC), durante la pandemia la Línea de la Vida amplió su cobertura para dar respuesta no sólo a problemas por uso de sustancias, sino en general, a problemas de salud mental con incidencia durante la emergencia sanitaria. A partir de marzo de 2020, el Grupo Técnico de Trabajo de Salud Mental de la Secretaría de Salud ajustó sus estrategias para dar respuesta a las solicitudes de atención recibidas a través de este medio, a fin de dar cabida a la colaboración de instituciones y organizaciones que ofrecieron su apoyo para atender una demanda que mostraba un in-Los trastornos reportados más frecuentemente en el mundo son ansiedad y depresión, encontrándose tasas más altas de ansiedad entre la población de adultos jóvenes, mujeres, sectores económicamente vulnerables (Elbay et al, 2020;Hyland et al, 2020;Lin et al, 2020;Mental Health America, 2020;Qiu et al, 2020;Özdin & Bayrak Özdin, 2020;Wong et al, 2020), pacientes con un diagnóstico psiquiátrico previo (Mazza, De Lorenzo, et al, 2020) y personal de salud involucrado directa o indirectamente con la atención de población afectada por la epidemia (Luo et al, 2020;Mosheva et al, 2020;Torales et al, 2020;Savitsky et al, 2020). Por el contrario, destaca que adultos mayores, uno de los grupos más afectados en términos de mortalidad atribuible a COVID-19, muestran, según Bruine de Bruin (2020), niveles menores de depresión y ansiedad que adultos jóvenes.…”
Section: Introductionunclassified
See 1 more Smart Citation